Uptake of cervical cancer screening service and associated factors among age-eligible women in Ethiopia: systematic review and meta-analysis - Asteray Assmie Ayenew; Biruk Ferede Zewdu; Azezu Asres Nigussie (Infectious Agents and Cancer, 2020)
Abstract Background Cervical cancer is the leading cause of cancer deaths among women in developing countries. Since cervical cancer is a preventable disease, screening is an important control and prevention strategy, recommended by the World Health Organization (WHO) for all women aged 30 years and older, and even earlier for some high-risk women. Therefore the aim of this study was to assess the uptake of cervical cancer screening among age-eligible women in Ethiopia. Method Review identification was performed through the search of online databases PubMed, Google Scholar, HINARI, EMBASE, Science Direct, Cochrane library, African Journals, and other gray and online repository accessed studies were searched using different search engines. For critical appraisal of studies, Newcastle-Ottawa Quality Assessment Scale (NOS) was used. The analysis was conducted by using STATA 11 software. To test the heterogeneity of studies, the Cochran Q test and I2 test statistics were used. To detect publication bias of the studies, the funnel plot and Egger’s test were used. The pooled prevalence of cervical cancer screening and the odds ratio (OR) with a 95% confidence interval were presented using forest plots. Result Twenty-four studies with a total of 14,582 age-eligible women were included in this meta-analysis. The pooled national level of cervical cancer screening among age-eligible women in Ethiopia was 13.46% (95%CI:11.06,15.86). Knowledge on cervical cancer and screening (OR = 4.01,95%CI:2.76,5.92), history of multiple sexual partners (OR = 5.01, 95%CI:2.61,9.61), women’s age (OR = 4.58, 95%CI:2.81,7.46), history of sexually transmitted disease (OR = 4.83,95%CI:3.02,7.73), Perceived susceptibility to cervical cancer (OR = 3.59, 95%CI:1.99,6.48), getting advice from health care providers (OR = 4.58, 95%CI:3.26, 6.43), women’s educational level (OR = 6.68,95%CI:4.61,9.68), women’s attitude towards cervical cancer and screening (OR = 3.42, 95%CI:2.88,4.06) were the determinant factors of cervical cancer screening uptake among age-eligible women in Ethiopia. Conclusion The pooled prevalence of cervical cancer screening was remarkably low among age-eligible women in Ethiopia. Thus, to increase the uptake of cervical cancer screening among age-eligible women regularly, it is better to create awareness programs for early detection and treatment of cervical cancer, and educational interventions that teach the step-by-step practice of cervical screening to increase women’s attitude for screening. Additionally, it is better to inform every woman is susceptible to cervical cancer, especially after starting sexual intercourse, and screening remains fundamental in the fight against cervical cancer before becoming invasive. Moreover, counseling and improving the confidence of women by health care providers to undergo screening is recommended.